2008
DOI: 10.1093/aob/mcn085
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to flooding in upland and lowland ecotypes of Cyperus rotundus, a troublesome sedge weed of rice: tuber morphology and carbohydrate metabolism

Abstract: Tolerance of lowland C. rotundus of flooding may be attributed to large carbohydrate content and amylase activity, and the ability to maintain high levels of soluble sugars in the tubers during germination and early growth. This is coupled with the modulation of ADH and PDC activities during germination, possibly to control the use of carbohydrate reserves and sustain substrate supply in order to avoid starvation and death of seedlings with prolonged flooding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 20 publications
6
61
0
5
Order By: Relevance
“…Las plantas expuestas a condiciones anaeróbicas pueden cambiar su metabolismo de respiración aeróbica a la vía de la fermentación, como un mecanismo adaptativo a la carencia de oxígeno (Fukao et al, 2003;Peña-Fronteras et al, 2008). En ausencia de oxígeno, el ciclo del ácido cítri-co y la fosforilación oxidativa no funcionan y la glicolisis se detiene por la limitación en el contenido de NAD + .…”
Section: Respuesta Bioquímicaunclassified
See 3 more Smart Citations
“…Las plantas expuestas a condiciones anaeróbicas pueden cambiar su metabolismo de respiración aeróbica a la vía de la fermentación, como un mecanismo adaptativo a la carencia de oxígeno (Fukao et al, 2003;Peña-Fronteras et al, 2008). En ausencia de oxígeno, el ciclo del ácido cítri-co y la fosforilación oxidativa no funcionan y la glicolisis se detiene por la limitación en el contenido de NAD + .…”
Section: Respuesta Bioquímicaunclassified
“…La enzima PDC cataliza la conversión de piruvato a acetaldehído en el primer paso en la vía de la fermentación alcohólica (Yin et al, 2009). Luego el acetaldehído es reducido a etanol en una reacción catalizada por la ADH, donde el NADH es oxidado (figura 1) (Kato-Noguchi et al, 2000;Peña-Fronteras et al, 2008), la producción de etanol es menos tóxica para la planta ya que este puede difundir fuera de la célula (Taiz y Zeiger, 2010). La fermentación etanólica no necesita ser precedida por la fermentación del lactato (Kato-Noguchi et al, 2000;Mohanty y Ong, 2001) y el factor más limitante para esta vía, bajo condiciones de déficit de oxígeno, no es la ADH sino la cantidad reducida de PDC (Kato-Noguchi et al, 2000).…”
Section: Respuesta De Las Plantas a Estrés Por Inundaciónunclassified
See 2 more Smart Citations
“…For instance, Lenssen et al (2004) found that populations of the clonal plant Ranunculus reptans from a lakeside microhabitat and a landside microhabitat differed significantly in traits related to overall fitness, indicating that flooding induced a local adaptation of the species. Peña-Fronteras et al (2009), working with Cyperus rotundus, a troublesome sedge weed of rice, also found considerable differences in tuber morphology and carbohydrate metabolism when comparing ecotypes from upland and lowland sites. However, the most striking example was reported for Himatanthus sucuuba.…”
Section: Introductionmentioning
confidence: 99%